Energy Consumption Analysis of Fuel Cell Commercial Heavy-Duty Truck with Waste Heat Utilization Under Low-Temperature Environment - Fujian Liu; Qiao Zhu; Dawei Dong; Zhichao Zhao; Xiuping Zhu; Kunyi Feng; Haifeng Dai; Hao Yuan (Energies)
Waste heat utilization in fuel cell vehicles represents a critical technology for enhancing overall energy utilization efficiency and environmental adaptability, which reduces auxiliary heating consumption, extends driving range, and minimizes thermal management parasitic losses, holding significance for promoting application of fuel cell commercial vehicles. This study investigates a 49-ton fuel cell heavy-duty truck equipped with waste heat recovery capability, conducting vehicle energy flow experiments under multiple ambient temperatures (including 7 °C, <semantics>−7</semantics> °C and <semantics>−25</semantics> °C extreme cold conditions), varying load conditions, and waste heat recovery mode switching, with focused analysis on the energy consumption and temperature response of the waste heat recover critical components, to evaluate the energy utilization of fuel cell waste heat. Experimental results demonstrate the substantial impact of waste heat recovery function on the proportion of the warm air positive temperature coefficient (PTC) energy consumption on total energy consumption, showing that deactivating waste heat recovery increased the PTC energy consumption obviously. Besides, activating the waste heat recovery function contributes to elevated the stack radiator outlet temperature under low-temperature operating conditions.